Mourning, activism, and queer desires: Ni Una Menos and Carri’s Las hijas del fuego - Sosa, Cecilia (2021)
Argentina’s neoconservative backlash (2015–2019) has rather paradoxically been marked by an unprecedented entanglement of ongoing memory struggles and a recent feminist awakening. A critical reading of this entwining traces the queer reworking of dictatorship trauma during the Kirchnerist administrations (2003–2015) and explores the way the post-2015 cycle nurtured a feminist irruption that contested long-standing forms of patriarchy. The feminist movement Ni Una Menos has transitioned from victimization to joy. Albertina Carri’s lesbian-porn fictional film Las hijas del fuego (2018) can be read as an expression of a novel amalgam of disappearance, sexuality, and politics. The spirit of contagion radiated by the film sheds light on the “revolution of the daughters” now taking place in the streets.